Mobile special forces in the structure of the Federal Service of the National Guard Troops of the Russian Federation: genesis and current issues in normative and legal consolidation of activities - Olesya A. Timoshkina (Известия высших учебных заведений. Поволжский регион: Общественные науки, 2023)
Background. The article considers the issues of formation, legal regulation of the organization of mobile special forces activities of the Federal Service of the National Guard Troops of the Russian Federation, as one of the special units in its composition, performing the tasks of ensuring public safety and protecting public order during mass events, special operations, combat with terrorism and extremism, power support in the process of implementing joint activities with other law enforcement units. Legal acts regulating some aspects of the activity of mobile special forces units in the system of the Federal Service of the National Guard Troops of the Russian Federation are analyzed. Proposals are being formulated to improve the legislation governing the organization of the activities of specialpurpose mobile detachments. In recent years, a large-scale reform of some law enforcement agencies has been carried out in the Russian Federation, during which a number of issues have arisen that require a comprehensive study and solution. One of the activities of such a transformation is the issue of legal regulation of the transfer of a number of units and their functions from the Ministry of Internal Affairs of the Russian Federation to an established body – the Federal Service of the National Guard Troops of the Russian Federation, to which some special units that were previously part of the Ministry of Internal Affairs of Russia were transferred, including and detachments of mobile special forces. The solution of such problems is not possible without the assessment and analysis of the regulations governing the activities of these departments. The purpose of the work is to highlight the main milestones in the formation of mobile special forces from the moment of their creation to the present, to formulate some problems of normative consolidation of activities, and to analyze the legal acts regulating the activities of mobile special forces. Materials and methods. In the course of studying the historical aspect of activity and analyzing legal sources, the historical and legal method was used; analysis and synthesis were used to summarize the results. Results. Legal acts regulating the activities of mobile special forces units as part of the Federal Service of the National Guard Troops of the Russian Federation are analyzed, a historical analysis of formation is carried out. Proposals have been formulated to improve the legislation governing some aspects of their activities. Conclusions. Currently, mobile special forces of the Federal Service of the National Guard Troops of the Russian Federation are a reliable tool for providing power support to the federal executive authorities and other state structures of the Russian Federation in the exercise of their functions to ensure law and order and stability on the territory of the Russian Federation. Those tasks, the implementation of which is entrusted to mobile special forces in the current conditions of exacerbation of the foreign political situation, are of particular importance. The activities of these units should be comprehensively regulated and clearly organized.